Cheilitis granulomatosa (Miescher granulomatous macrocheilitis) with Down syndrome: A rare alliance - Balwinder Kaur Brar; B B Mahajan; Nidhi Kamra (Wolters Kluwer Medknow Publications, 2016)
Melkersson-Rosenthal syndrome comprises of the triad of orofacial swelling, facial paralysis, and fissured tongue. It may present in monosymptomatic form as Meischer granulomatous cheilitis. Herein we report an unusual association of Meischer's cheilitis with Down syndrome.